2018
DOI: 10.1021/acs.macromol.7b02367
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation of Thermoplastic Polyurethanes under Large Tensile Deformation

Abstract: Thermoplastic polyurethanes (TPUs) are useful materials for numerous applications due in part to their outstanding resilience and ability to dissipate energy under large mechanical deformation. However, the mechanistic understanding of the origins of these mechanical properties at the molecular level remains elusive, largely due to the complex, heterogeneous structure of these materials, which arises from the segregation of chemically distinct segments into hard and soft domains. In this work, molecular simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 39 publications
5
69
1
Order By: Relevance
“…Whereas, little attention is given to the mechanism of high strain hardening ratio for elastomers. For most elastomers, strain‐induced crystallizations are usually found during deformation . Then the crystallization zones present hard inclusions in elastomers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, little attention is given to the mechanism of high strain hardening ratio for elastomers. For most elastomers, strain‐induced crystallizations are usually found during deformation . Then the crystallization zones present hard inclusions in elastomers.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular simulations were also used to study the molecular‐level mechanism of mechanical response under large tensile for yielding, toughening and Mullins effect, and some mechanisms were found for yielding and plastic flow. They were categorized as (a) cavitation, (b) chain pull‐out, (c) localized melting with shear band formation, and (d) block slip …”
Section: Introductionmentioning
confidence: 99%
“…For this study of TPU response in compression, we use the same systems and methods as described in our previous report of TPU response in extension, 11 where a more detailed explanation on model construction can be found. For the sake of completeness, the details of models construction are briefly recapped below, but the reader is referred to the previous report 11 for a more complete description. We use the Interphase Monte Carlo (IMC) method of Rutledge and co-workers [13][14][15][16][17][18][19] as implemented in the EMC (Enhanced Monte Carlo) 16 software (version 9.3.7) to construct the model.…”
Section: System and Methodsmentioning
confidence: 99%
“…To gain insight into the complex behaviour of semicrystalline polymers, atomistic modelling is a useful numerical modelling tool that has been widely used in the literature [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Most of these works have been based on simplified and coarse-grained interaction models, such as the united atom (UA) interaction model.…”
Section: Introductionmentioning
confidence: 99%
“…Among the aforementioned works, Rutledge and co-workers recently published a series of papers dealing with molecular dynamics (MD) modelling of yielding of PE [25][26][27][28][29][30] and other semi-crystalline polymers, such as polyurethane [31,32] and polyether [33]. These investigations have revealed that there is a strain rate dependence that dictates the observed stressstrain behaviour and yielding mechanisms [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%